Corporate Liability of Energy/Natural Resources Companies at National Law for Breach of International Human Rights Norms - Olivier Salas-Fouksmann (UCL Journal of Law and Jurisprudence, 2015)
This paper examines the challenges posed by domestic judicial mechanisms to address the liability of natural resources companies for human rights abuses and environmentally harmful activities, through the foreign operations of their subsidiaries. It explores the conceptual difficulties underlying the notion of liability at national law for violating international norms and it highlights current challenges raised by the arguments made before the United States Supreme Court in the Kiobel case to stop victims of human rights violations from bringing claims under the Alien Tort Statute for corporate abuses committed in the territory of a foreign state. The paper raises the concern that corporate impunity for violation of human rights norms might become justified at national law by the difficulty to find sources of international law to hold corporations liable for violation of international norms. It finally sheds light on enforcement challenges for establishing private rights of action and determining liability of corporate actors, arguing that the reluctance of national courts to expand principles of corporate liability and extraterritorial jurisdiction for corporate harms might affect long-term reforms to hold natural resources companies liable for their abuse of international human rights norms. Read more